Cyanine-dyad molecular probe for the simultaneous profiling of the evolution of multiple radical species during bacterial infections - Wang, Zhimin (2022)
Real-time monitoring of the evolution of bacterial infection-associated multiple radical species is critical to accurately profile the pathogenesis and host-defense mechanisms. Here, we present a unique dual wavelength near-infrared (NIR) cyanine-dyad molecular probe (HCy5-Cy7) for simultaneous monitoring of reactive oxygen and nitrogen species (RONS) variations both in vitro and in vivo. HCy5-Cy7 specifically turns on its fluorescence at 660 nm via superoxide or hydroxyl radical (O2 .- , . OH)-mediated oxidation of reduced HCy5 moiety to Cy5, while peroxynitrite or hypochlorous species (ONOO- , ClO- )-induced Cy7 structural degradation causes the emission turn-off at 800 nm. Such multispectral but reverse signal responses allow multiplex manifestation of in situ oxidative and nitrosative stress events during the pathogenic and defensive processes in both bacteria-infected macrophage cells and living mice. Most importantly, this study may also provide new perspectives for understanding the bacterial pathogenesis and advancing the precision medicine against infectious diseases.